Language Regression, Autism, and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The records of 196 consecutive children (143 males and 53 females) with language regression evaluated between 1988 and 1994 by a child neurologist were analyzed at the Department of Neurology, Albert Einstein College of Medicine, Bronx, NY.